Multilayer Lateral Heterostructures of Van Der Waals Crystals with Sharp, Carrier–Transparent Interfaces. Issue 3 (23rd November 2021) - Sutter, Eli; Unocic, Raymond R.; Idrobo, Juan‐Carlos; Sutter, Peter
Abstract: Research on engineered materials that integrate different 2D crystals has largely focused on two prototypical heterostructures: Vertical van der Waals stacks and lateral heterostructures of covalently stitched monolayers. Extending lateral integration to few layer or even multilayer van der Waals crystals could enable architectures that combine the superior light absorption and photonic properties of thicker crystals with close proximity to interfaces and efficient carrier separation within the layers, potentially benefiting applications such as photovoltaics. Here, the realization of multilayer heterstructures of the van der Waals semiconductors SnS and GeS with lateral interfaces spanning up to several hundred individual layers is demonstrated. Structural and chemical imaging identifies 110 interfaces that are perpendicular to the (001) layer plane and are laterally localized and sharp on a 10 nm scale across the entire thickness. Cathodoluminescence spectroscopy provides evidence for a facile transfer of electron‐hole pairs across the lateral interfaces, indicating covalent stitching with high electronic quality and a low density of recombination centers. Abstract : Multilayer heterostructures with localized and sharp lateral interfaces across hundreds of individual van der Waals layers are realized from the anisotropic layered semiconductors SnS and GeS. Cathodoluminescence spectroscopy shows the transfer of electron–hole pairs across the lateral interfaces, demonstrating excellent connectivity without interfacial recombination. The results are promising for applications benefiting from thick layered crystals combined with in‐plane carrier manipulation.